Ciudades intermedias y desconcentración territorial: propósitos, alcances y viabilidad - De Mattos, Carlos A (Revista EURE - Revista de Estudios Urbano Regionales, 1984)
Carlos A. de Mattos says that several proposals have recently appeared regarding the reordering of human settlements, oriented towards the strenghtening of medium size centers, in search of a more balanced distribution of population and economic activities. He concentrates in the analysis og the main characteristics they involve, its purposes, justification and viability. His starting point is a short presentation of the main features of the prevailing territorial structures in Latin America, as well as of the problems commonly attached to them. The author ends by attempting to propose several alternative ways of backing up the development of these medium size urban centers based on his analysis of the restrictions that have to be faced in such process.